Application of RASCH measurement model in quality evaluation of Shariah Compliant Gold Investment (SCGI) instrument / Najahudin Lateh and Ghafarullahhuddin Din - Najahudin Lateh; Ghafarullahhuddin Din (Academy of Contemporary Islamic Studies, 2016)
This paper describes the process of assessing the validity and reliability of a new instrument namely Shariah Compliant Gold Investment (SCGI). The instrument consists of 33 items that are embedded in three dimensions and was administered to 27 Malaysian investors and investment institutions. Rasch model was used to examine the validity of items by two criteria (1) point measure correlation (PTMEA CORR) and (2) fit statistics (infit/outfit MNSQ and z-std). The findings indicated that the reliability value for the respondents and items are high with r = 0.91 and r = 0.81 respectively with Cronbach alpha 0.93. At the same time, the item separation is 2.07 while the person separation is 3.15. As for the items polarity, most of the items contributed to the measurement as all of the PTMEA CORR values are positive (+0.44 logit to +1.66 logit) except for the A03 item (0.17 logit). The fit item testing indicated that the value of the sum of the mean of infit MNSQ and SD was between +0.68 logit to +1.30 logit. Only one item (A03) falls in the range of elimination due to negative value of PTMEA CORR and z-std > 2.0. The results suggested the item to be removed, retaining the balance of 32 items.